<u>Answer:</u>
The correct answer option is D. ![-5^x+3x-2](https://tex.z-dn.net/?f=-5%5Ex%2B3x-2)
<u>Step-by-step-explanation:</u>
We are given the following two functions:
and
![g(x)= -3x-2](https://tex.z-dn.net/?f=g%28x%29%3D%20-3x-2)
We are to find
so we will subtract the function g from function f, arrange the like terms together and combine them like shown below to get:
![(f-g)(x) =(-5^x-4)-(-3x-2)](https://tex.z-dn.net/?f=%28f-g%29%28x%29%20%3D%28-5%5Ex-4%29-%28-3x-2%29)
![(f-g)(x)=-5^x-4+3x+2](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D-5%5Ex-4%2B3x%2B2)
![(f-g)(x)=-5^x+3x-2](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D-5%5Ex%2B3x-2)
Therefore,
is equal to
so the correct answer option is D.
.
Answer:
12
Step-by-step explanation:
ΔBAD is similar to ΔCBD. So we can write a proportion:
BD / CD = AD / BD
h / 16 = 9 / h
h² = 144
h = 12
Answer:
8 and 6
Step-by-step explanation:
8 * 6 = 48
8 + 6 = 14
The answer is B due to the corresponding 130